Study of Teacher Behavior in Using the Google Classroom Application During a Pandemic: Analysis Using Technology Acceptance Models - Euis Widanengsih (Sean Institute, 2022)
This research studies teacher behaviour using the Google Classroom application using Technology Acceptance Models. The data used in this study are primary data from 27 respondents, collected data with a scale questionnaire. The sampling method uses a purposive sampling method with criteria for teachers in Jakarta and its surroundings who use Google Classroom to teach during the pandemic. The survey was conducted in September 2022. The results of the study show that Perceived Usefulness is significant for Attitude Toward Use, Perceived Ease of Use is significant for Attitude Toward Use, Perceived usefulness does not significantly affect Behavioral Intentions, and Attitude Toward Use significantly influences Behavioral Intentions